Social representations of transgender people (transvestites and transexuals) about violence - Ribeiro, Luiz Paulo (2019)
This study investigated the social representations about violence of the transgender population in Belo Horizonte, Minas Gerais, Southeastern Brazil. Semi-structured interviews and content analysis were used combined with lexical analysis through Iramuteq software. Nine transgender people (transvestites and transsexuals) were chosen for the interview based on convenience sampling. The results show that the anchorages and objectifications of social representations are organized into four categories: (a) experiences of violence (b) institutions and traditional process, (c) identity processes (d) and body and social life. Consequently, the anchorages and objectification of the social representationsof violence are related to the transitional process, the individual and social experiences to which these people are subjected that could be related to the acceptance and resistance to violence.